Experimental study on influencing factors of fracture propagation in fractured carbonate rocks. (February 2020) - Guo, Yintong; Hou, Longfei; Yao, Yiming; Zuo, Luo; Wu, Zhiying; Wang, Lei
Abstract: Carbonate reservoirs show poor porosity and permeability in matrix, it is necessary to improve the permeability channel through reservoir reconstruction. The influence of different fracturing parameters on fracture propagation of carbonate rock is studied, which is of great significance to hydraulic fracturing design of carbonate rock. In this paper, a series of hydraulic fracturing experiments were performed under different conditions, the fracturing pump pressure curve, radial deformation characteristics and fracture morphology were studied and analyzed. The results show that: (1) The rock-acid reaction between gelled acid and carbonate rock produces etching wormholes, changes the pore structure and weakens the mechanical parameters of carbonate rocks, which is conducive to reducing fracturing pressure and increasing fracture complexity; (2) The types of fracturing fluids and the viscosity significantly affect fracturing rupture pressure and the width of the fracture. Under the same in-situ stress and flow rate conditions, the fracturing rupture pressure of slick water is the lowest and that of guar gum is the highest; (3) Composite fracturing can improve the complexity of fractures in carbonate reservoir, for carbonate rocks with fracture developed near wellbore, complex fracturing fractures can be made by slick water fracturing, and main fracturing surfaces can be eroded by gelled acid to improve the width and increase the roughness. (4) To solve the problem of high fracturing pressure under high in-situ stress, gelled acid can be used for pretreatment to reduce fracturing pressure, and then non-reactive fluid, slick water or guar gum can be used for fracturing. Our research findings provide a reliable basis for deep fractured carbonate reservoir reconstruction. Highlights: The fracturing fluids affect fracturing rupture pressure and the width of the fracture. Composite fracturing can improve the effect of carbonate reservoir reconstruction. Main fracturing surfaces can be eroded by gelled acid to improve the width and increase the roughness.